Effect of Gait Imagery Tasks on Lower Limb Muscle Activity With Respect to Body Posture. Issue 2 (April 2016) - Kolářová, Barbora; Krobot, Alois; Polehlová, Kamila; Hluštík, Petr; Richards, Jim D.
The objective of this study was to evaluate the effect of gait imagery tasks on lower limb muscle activity with respect to body posture. The sitting and standing position and lower limb muscle activity were evaluated in 27 healthy female students (24.4 ± 1.3 years, 167.2 ± 5.2 cm, 60.10 ± 6.4 kg). Surface electromyography was assessed during rest and in three different experimental conditions using mental imagery. These included a rhythmic gait, rhythmic gait simultaneously with observation of a model, and rhythmic gait after performing rhythmic gait. The normalized root mean square EMG values with respect to corresponding rest position were compared using non-parametric statistics. Standing gait imagery tasks had facilitatory effect on proximal lower limb muscle activity. However, electromyography activity of distal leg muscles decreased for all gait imagery tasks in the sitting position, when the proprioceptive feedback was less appropriate. For subsequent gait motor imagery tasks, the muscle activity decreased, probably as result of habituation. In conclusion, the effect of motor imagery on muscle activity appears to depend on relative strength of facilitatory and inhibitory inputs.